The impact of economic factors on financial performance in Malaysia - Wong Vui Ken; Saizal Pinjaman (Faculty of Business, Economics and Accountancy, 2021)
This research determines the impact of microeconomic, industry-specific, and macroeconomic variables on the financial performance of the economic sector in Malaysia, namely construction, consumer products and services, energy, health care, industrial products and services, plantation, property, technology, telecommunications and media, transportation and logistics, and utilities. The research used panel data analysis for all 11 economic sectors in Bursa Malaysia and covered the period from 2010 to 2019. It is identified that the lagged effect of financial performance has significant impact on financial performance for the overall and 3 specific economic sectors such as consumer products and services, industrial products and services, and property. Microeconomic and macroeconomic variables meanwhile lead to different impacts on economic sectors. The findings benefit various parties such as investors and policymakers. Apart from that, information obtained from the analysis can also be used for future research.